Research on the characteristics of Klein–Cook parameter and diffraction efficiency of acousto-optic interaction for low-frequency ultrasonic in the liquid - Gao, Jing; Han, Guang; Zhu, Jianzhuo (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
We have investigated the characteristics of acousto-optic interaction for low-frequency ultrasonic wave in a liquid. Based on the coupling wave equation of acousto-optic interaction, the diffraction light characteristics for normal incidence at small parameter Q have been discussed. The parameter Q with respect to acousto-optic interaction length, ultrasonic frequency, water temperature, and the concentration of sucrose solution have been analyzed, which is an important physical quantity and reflects the degree of mismatch in the acousto-optic interaction. The diffraction efficiencies for different parameters Q, incident angles and phase shifts have been calculated. The results of our work provide theoretical basis for further study of the acousto-optic effect in the liquid.
Optica Applicata, Vol. 51, 2021, nr 3, s. 445-456
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; acousto-optic interaction; Klein–Cook parameter; Raman–Nath diffraction; diffraction efficiency